Design and fabrication of the assignment tray - Mohd Shahril, Khamis (2007)
Nowadays, assignment tray and paper rack was use widespread in whole world. Especially as a student, they use assignment tray to store their paper work and assignment sheet. However, there are some things that can't solve by existing assignment tray, for example, can't keep lots of paper, sheet of paper that kept on that uncovered, sheet of paper scatter in the air, can only kept the paper and not suitable for writing equipments, and so on. That's why we need the new concept of the assignment tray. The main feature of this projects assignment tray was the flexibility to become single stage and double-decker. The idea was appear because of the lack functionality in the existing assignment tray in market. The purpose of design this assignment tray was to ensure the documents or assignment sheet is being kept securely. Drawer was put as the additional feature to get the extra place to keep other items. There are several processes involved during the design and fabrication process of this assignment tray. The best feature and shape of assignment tray was designed in order to get the smart and modern look of product. Several aspects needed the full commitment in order to maintain this project run as same as project planning and finished on time.